The influence of 2- chlorodeoxyadenosine in combination with tumour necrosis factor-α or its mutein on murine leukaemias L1210 and P388 - J. Góra-Tybor; K. Warzocha; T. Robak (Mediators of Inflammation)
We investigated the influence of 2-chlorodeoxyadenosine (2-CdA) in combination with tumour necrosis factor-α (TNFα) or its mutein VI, which differs from the native molecule by N-terminal amino acid composition, on the survival time of mice inoculated with leukaemia L1210 or P388. Groups of mice with leukaemia L1210 and P388 receiving 2-CdA combined with TNFα had shorter survival times than animals treated with these agents separately. In contrast, the administration of 2-CdA in conjunction with mutein VI, prolonged the survival of mice inoculated with these leukaemias as compared with animals receiving these agents separately. The results of the present study emphasize the importance of the biological activity of the TNFα molecule N-terminus.